P5_4 Martian Tripods In All Their Nuclear Glory - Cox, Tom; Fernandez, Keaton Penn; Mead, Lara; Seagrave, Joshua (Physics Special Topics, 2020)
In the terrifying 2005 movie adaption of the famous H. G. Wells “The War of the Worlds”, the Martians use machines of mass destruction in the form of giant three-legged walkers with powerfulheat rays to vaporise humans. In this paper we calculate how much uranium-235 would produce enough energy from nuclear fission, to not only vaporise a human but also cause human extinction. We found that 0.0363 g of U235 is required to completely vaporise a 78 kg human, and 2.37×10^5 kg of U235 to completely eradicate humanity. We found that one tripod would have to undergo nuclear fission for 1145.2 years to produce enough energy for global extinction.